Rancang Bangun Sistem Informasi Kearsipan Surat Masuk Dan Surat Keluar Berbasis Web Menggunakan Metode Agile Di Universitas Flores - Roswita dambus; Ferdinandus Lidang Witi; L.B Finansius Mando (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Abstract The design of a web-based archiving information system for incoming and outgoing letters at the University of Flores aims to help facilitate the letter archiving process such as recording the letter number, date of receipt, date of incoming letter, subject, origin of the letter and also the disposition of letters is still done manually using a ledger. and Microsoft Excel, which often causes many problems, which are easily damaged and lost and the search process takes a very long time, sometimes errors or errors occur on the disposition sheet. Therefore, to overcome these problems the authors conducted research and the method used in this study was the Agile method starting from the planning, implementation, software testing, documentation, deployment, and maintenance stages. In this study, the system testing method used is the Black Box method of testing a software without having to pay attention to software details. Keywords: Information System, Archiving incoming and outgoing mail, Agile Method, Black Box Testing Method